PENGARUH TANAH MINERAL DAN PUPUK FERTIPHOS TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS PADA LAHAN GAMBUT - Suprapto, Suprapto; Radian, Radian; Abdurrahman, Tatang (Fakultas Pertanian, Universitas Janabadra, 2024)
Sweet corn (Zea mays, L) is an agricultural commodity that has the potential to be cultivated and developed. This study aimed at the interaction and the best dose of mineral soil and fertiphos fertilizer on the growth and yield of sweet corn on peatlands. The research was conducted at Banjar Sari Hamlet, Rasau Jaya II Village, Rasau Jaya District, Kubu Raya Regency. This research was conducted in May until July 2023. The research was complete randomized design (CRD) method consisting of two factors, the first factor is mineral soil consisting of 3 levels, namely, m₁ = 5 tons/ha equivalent to 2.5 kg/plot, m2 = 10 tons/ha equivalent to 5 kg/plot, m3 = 15 tons/ha equivalent to 7.5 kg/plot and the second factor, fertiphos fertilizer which consists of 3 levels, namely, pi 100kg/ha, equivalent to 50 g per plot, p2 = 200kg/ha equivalent to 100 g/plot, p3 = 300 kg/ha equivalent to 150 g/plot, each treatment combination in this study was repeated 3 times. The results showed that there was an interaction between mineral soil and fertiphos fertilizer in increasing cob length and cob weight per plot. Application of mineral soil at a dose of 15 tons in a ha gave the best results in producing cob length, cob diameter, cob weight per plot. Ferthipos fertilizer at a dose of 100 kg in a hectare can produce growth and yield of sweet corn on peat soil.